Short-term variability in ocular biometry and the impact of preoperative dry eye - Sanghyuk Ahn; Youngsub Eom; Jong Suk Song; Dong Hyun Kim (Scientific Reports)
Abstract This study aimed to investigate the short-term variability of ocular biometric measurements and to analyze the factors associated with high variability of biometric values in patients with cataract. This retrospective study included 60 eyes of 60 patients who underwent ocular biometry twice with the IOLMaster 700 (March to November 2023). Ocular surface parameters included tear film break-up time (TBUT), corneal and conjunctival staining scores (CSS/ConSS). Refractive surprise was defined as a mean absolute error exceeding 0.5 diopter (D). Participants included 22 men and 38 women with a mean age of 70.6 ± 8.4 years. The variability of mean keratometric (K) values and astigmatism showed notable variability compared to axial length (mean K: 0.18 ± 0.17D, astigmatism: 0.21 ± 0.26D, axial length: 0.01 ± 0.01 mm). A decreased TBUT and increased CSS were significantly associated with high variability (≥ 0.25D) of mean K (p = 0.040/0.008). The high K variability group (≥ 0.25D) revealed a significantly higher incidence of refractive surprise (> 0.5D) compared with the low K variability group (< 0.25D) (45.5%/17.9%, p = 0.037). Preoperative lower TBUT and higher CSS influenced the variability of K values in ocular biometry and may be related with postoperative refractive surprise due to erroneous K values.